2010
DOI: 10.1186/1756-3305-3-56
|View full text |Cite
|
Sign up to set email alerts
|

Larval trematode communities in Radix auricularia and Lymnaea stagnalis in a reservoir system of the Ruhr River

Abstract: BackgroundAnalysis of the data available from traditional faunistic approaches to mollusc-trematode systems covering large spatial and/or temporal scales in Europe convinced us that a parasite community approach in well-defined aquatic ecosystems is essential for the substantial advancement of our understanding of the parasite response to anthropogenic pressures in urbanised areas which are typical on a European scale. Here we describe communities of larval trematodes in two lymnaeid species, Radix auricularia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 25 publications
5
38
1
2
Order By: Relevance
“…; Faltýnková et al [24] also provided this number for E. revolutum ex L. stagnalis . It is worth noting that recent field studies indicate that E. revolutum most commonly occurs in L. stagnalis in Europe [23,24], infections with this species have occasionally been reported in the past from R. auricularia , R. peregra and R. ovata (Draparnaud, 1805) [22,37-45]. Further molecular study would reveal whether Echinostoma spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Faltýnková et al [24] also provided this number for E. revolutum ex L. stagnalis . It is worth noting that recent field studies indicate that E. revolutum most commonly occurs in L. stagnalis in Europe [23,24], infections with this species have occasionally been reported in the past from R. auricularia , R. peregra and R. ovata (Draparnaud, 1805) [22,37-45]. Further molecular study would reveal whether Echinostoma spp.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of the digeneans parasitising molluscs in central and northern Europe we found that Radix auricularia (Linnaeus, 1758), Radix peregra (Müller, 1774) and Stagnicola palustris (Müller, 1774) were infected with larval stages of two species of the Echinostoma ‘ revolutum ’ complex of cryptic species, one resembling E. revolutum sensu stricto (s.s.) and one undescribed species (see also [23]). Here we describe the cercariae of these two species and provide morphological and molecular evidence for their delimitation.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently the use of transcriptomics to integrate eco-toxicogenomics into marine health evaluation has been assessed [107] via contamination-associated gene expression markers. Parasites themselves have been shown to be useful markers of ecosystem status and its response to change [108,109], including response to climate change [110]. The employment of eDNA methods for such studies can be very effective if appropriate sampling and molecular strategies are chosen (Boxes 1 and 2), both reducing sampling effort and maximizing sampling coverage.…”
Section: Potential For Development Of Edna Methods In Parasitologymentioning
confidence: 99%
“…Snail-trematode systems can be used to assess anthropogenic change (e.g. Morley 2007;Soldánová et al 2010), the effect of wetland restoration projects (e.g. Huspeni and Lafferty 2004;Morley and Lewis 2007) and the environmental impacts of global warming (Poulin 2006;Poulin and Mouritsen 2006).…”
Section: Faunas and Communitiesmentioning
confidence: 99%
“…In spite of their significant roles in freshwater trophic webs both as grazers and prey and in parasite transmission, there is a lack of quantitative information on the composition and structure of larval communities in mollusc hosts within individual freshwater ecosystems in Europe (but see Faltýnková et al 2008b;Soldánová et al 2010). The numerous faunistic studies listed in Faltýnková et al (2007Faltýnková et al ( , 2008a and Żbikowska and Nowak (2009) report summed data on the parasite richness and prevalence in these hosts over large temporal and spatial scales or both.…”
Section: Introductionmentioning
confidence: 97%